Risk factors for moisture damage presence and severity in Finnish homes - Jonathon Taylor; Anniina Salmela; Martin Täubel; Antti Heimlander; Anne M. Karvonen; Toni Pakkala; Jukka Lahdensivu; Juha Pekkanen (Buildings & Cities, 2023)
Moisture-damaged buildings are a prominent issue in Finland, but with limited information on damage prevalence, degree of severity and risk factors. This paper analyses 14,996 Finnish detached and semidetached houses that have undergone a standardised moisture assessment of interior spaces and at-risk structures inside the building envelope. Confirmed damage (a binary indicator of damage presence) and a damage index (an ordinal indicator of severity) were calculated for each home and their association with different building and area characteristics estimated. Frequently damaged structures include pre-1950s log walls, walls contacting soil, wooden ground floors and false plinths. Around 15% of surveyed houses had risk structure damage, 19% had at least one confirmed damage anywhere in the house and 49% had either confirmed, likely or possible damage. The greatest risk factor for confirmed damage was house age (odds ratio = 1.48 (95% confidence interval (CI) = 1.45–1.51) for each decade since construction), with nearly half of all houses built pre-1939 damaged. Other risk factors explained a third of the effect of building age, and included log external walls, fibreboard roofs, absence of mechanical ventilation, detached properties and wind-driven rain precipitation. Results can support targeted remediation efforts, protect health and estimate exposure–response relationships for moisture damage. Practice relevance Moisture damage in homes causes various health concerns for occupants, and in colder climates such as Finland such damage often occurs within the building structure. This study finds confirmed moisture damage in 19% of surveyed Finnish homes. Most damage was within the building structure, supporting the need for surveys investigating inside known-risk structures. Older homes had much higher damage risk, reflecting different construction methods and ageing, but also suggesting modern building standards are helping to reduce damage. Increased risk in higher wind-driven precipitation regions indicates a need for regulations and research that improve the resilience of all housing to the projected increases in driving rain from climate change. Understanding the building characteristics and structures that increase moisture risk can support targeted remediation and maintenance in vulnerable buildings, conserve older buildings and avoid demolition, and help protect occupant health.